Changes in protein structure monitored by use of gas‐phase hydrogen/deuterium exchange. Issue 16 (18th March 2015) - Beeston, Helen S.; Ault, James R.; Pringle, Steven D.; Brown, Jeffery M.; Ashcroft, Alison E.; Barran, Perdita; Cooper, Helen; Eyers, Claire
<x xml:space="preserve">Abstract</x> The study of protein conformation by solution‐phase hydrogen/deuterium exchange (HDX) coupled to MS is well documented. This involves monitoring the exchange of backbone amide protons with deuterium and provides details concerning the protein's tertiary structure. However, undesired back‐exchange during post‐HDX analyses can be difficult to control. Here, gas‐phase HDX‐MS, during which labile hydrogens on amino acid side chains are exchanged in sub‐millisecond time scales, has been employed to probe changes within protein structures. Addition of the solvent 2, 2, 2‐trifluoroethanol to a protein in solution can affect the structure of the protein, resulting in an increase in secondary and/or tertiary structure which is detected using circular dichroism. Using a Synapt G2‐S ESI‐mass spectrometer modified to allow deuterated ammonia into the transfer ion guide (situated between the ion mobility cell and the TOF analyser), gas‐phase HDX‐MS is shown to reflect minor structural changes experienced by the proteins β‐lactoglobulin and ubiquitin, as observed by the reduction in the level of deuterium incorporation. Additionally, the use of gas‐phase HDX‐MS to distinguish between co‐populated proteins conformers within a solution is demonstrated with the disordered protein calmodulin; the gas‐phase HDX‐MS results correspond directly with complementary data obtained by use of ion mobility spectrometry‐MS.